Komórki macierzyste siatkówki oka – istniejący stan badań, perspektywy terapeutyczne - Machalińska, Anna; Zuba-Surma, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
The latest research reports revealed the presence of stem/progenitor cells located in different regions of matured eye. They are able to differentiate into retinal pigment epithelium cells as well as neural structure of retina. These cells were identified in neurosensory retina, pigment epithelium and within cilliary body and iris epithelium. Moreover, it has been proved that Müller glia possess the potential of differentiation into retinal cells. These findings indicate the presence of potential mechanisms enabling retinal cell repopulation and retinal tissue regeneration. In the present work, the recent reports documenting the presence of different stem cell populations in eye have been reviewed, particularly focusing on recently identified very small embryonic-like stem cells (VSEL-SCs). The potential clinical applications of the residing stem cells and limitations of such therapeutic strategies have been also discussed.